Pengaruh Atmosphere Store, Diskon, Hedonic Shopping, Fashion Involment Dan Emosi Positif Sebagai Variabel Mediasi Terhadap Impulse Buying - Gamaya, Amritha; Suardana, Ida Bagus Raka (Jayapangus Press, 2024)
Clothing is a primary need so demand for apparel products continues to increase. The millennial generation is a generation that tends to be impulse consumers in the Asia Pacific region. Impulse buying behavior is a big opportunity for companies to increase their sales volume because buying without a plan or impulse buying is buyer behavior that is not based on a plan but because of the urge to own the goods they see. This research aims to (1) determine the influence of Store Atmosphere, Discounts, Hedonic Shopping, impulse buying, Fashion Involvement on impulse buying. (2) To determine the influence of Store Atmosphere, Discounts, Hedonic Shopping, and Fashion Involvement on impulse buying through positive emotions. (3) To determine the influence of positive emotions on impulse buying. This research is quantitative research in associative form. Research location at H&M Beachwalk Bali. The sampling technique in this research is a non-probability sampling technique used in this research is accidental sampling. The sample in this research was 208 samples. This research uses primary data through the use of questionnaires distributed to respondents. The analysis technique in this research uses Structural Equation Modeling (SEM) with SmartPLS software. The research results show that store atmosphere, discounts, hedonic shopping, fashion involvement, positive emotions have a positive and significant influence on impulse buying. Positive emotions as a partial mediating variable influence discounts, hedonic shopping, and fashion involvement on impulse buying.